Internship in Mercury Metalinks as Trader - Bokadia, Ritik (ATLAS SkillTech University, 2024)
1. The main continuous learning objective of my internship was to simultaneously upskill myself on the industrial equipment knowledge and other raw material procurement as per the client’s requirement. 2. Do research about other companies raw material requirements and using tally bills for the existing companies.
Project Report on Internship in Mercury Metalinks as Trader (2022-24) Under the Guidance of Prof. Sukanya Dixit
Keywords: Metalinks; Stocks; Market Research